Synthesis of 3-Alkyl Pyridinium Alkaloids from the Arctic Sponge Haliclona viscosa - Christoph Timm; Thorsten Mordhorst; Matthias Köck (Marine Drugs, 2010)
3-Alkyl pyridinium alkaloids (3-APAs) are common secondary metabolites in marine sponges of the order Haplosclerida. In recent years, our laboratory has isolated and synthesized several new members of this family such as haliclamines C–F, viscosamine, viscosaline and a cyclic monomer. All of them were isolated from the Arctic sponge Haliclona viscosa collected in Spitsbergen, Norway. In this article we report the syntheses of these secondary metabolites from Haliclona viscosa and related compounds and give a short overview of the bioactivity.